Use of Organic Materials to Maintain Soil Quality by Thai-Lao Rice Farmers in Northeast Thailand - Yodda, Sujitra; Laohasiriwong, Suwit; Rambo, A. Terry (Forest and Society, 2021)
Maintaining soil quality is a major problem for traditional farmers in the tropics. Many rely on organic amendments to enhance the productivity of their fields. However, indigenous knowledge about soil organic matter (SOM) and its management has received relatively little attention from researchers. This paper describes the use of organic materials to maintain soil quality by Thai-Lao farmers in a rice-growing village in Northeast Thailand. In-depth semi-structured interviews were conducted with twelve farmers to: 1) identify the indicators of soil fertility they employed; 2) inventory the organic materials they used; 3) determine changes in the use of amendments over time; and 4) understand their concept of SOM. They used many physical and biological indicators of soil quality. They used nine different organic materials: rice straw and stubble, cattle, buffalo and pig manure, rice husks, sunn hemp plants as green manure, charcoal, commercial compost, homemade compost, and tree leaf litter. Recently, use of livestock manure, rice husks, charcoal, and leaf litter has declined because of supply shortages. They do not appear to have a general concept of organic matter nor is there a commonly used word for “organic” in their language. Most of the farmers would use larger quantities of organic amendments but are constrained by their scarcity and high cost. Ways to increase local supplies of organic materials must be found if the government’s efforts to encourage the adoption of organic agriculture are to be successful.